Impact of climate change on crops, irrigation and hydropower in the Zambezi River Basin - Charles Fant; Yohannes Gebretsadik; Kenneth Strzepek (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The past reliance on historical observed weather patterns for future investment in basic infrastructure planning (e.g., irrigation schemes, hydropower plants, roads, etc.) has been questioned considerably in recent years. For this reason, efforts to study the impacts of a changing future climate based on climate projections from global circulation models has been popular, where the coupled model intercomparison project models, used in the Intergovernmental Panel for Climate Change Assessment Reports, are typically used. Studies tend to focus either on climate sensitivity, ignoring specific global circulation models predictions, or an effort is made to select a set of global circulation models for use in an impact study. Here, we present a method for quantifying the impacts on biophysical measures (surface water supply, crop production, flooding events, and hydropower generation) of the Zambezi River Basin countries using a large pool (6,800) of climate projections, which are based on the full set of the CMIP-3 GCMs (global circulation models ) and projected to 2050.
Keywords: Q54; O44; O55; 330; climate Change; Zambezi; southern Africa; investment risk; system model; water resource